Corporate social responsibility as an invention of public relation: a case of Econet and National Railways of Zimbabwe (NRZ) - Masuku, Caven; Moyo, Painos (Academic Journals, 2014)
This article examines the relationship and relevance of CSR and PR at Econet and NRZ in Zimbabwe. It focuses on how CSR can be perceived by people, especially in Zimbabwe as an invention of PR. CSR which is modern PR is guided by reciprocity between the corporations and their publics in an effort to create mutual understanding and goodwill between corporations and their publics. The study is based on two corporations namely, Econet and NRZ, whose business is immensely influenced by PR and CSR programs, which operate as effective communication strategies with their stakeholders for organisational success. PR is the core of the two corporations in Zimbabwe, essentially suitable for creating corporate citizenship to maximise profit. The study would be informed by four theories namely Carroll’s model of CSR, two-way symmetrical models, open systems approach and public opinion. Further, the study applies triangulation through the use of both qualitative and quantitative research methods to obtain information for reality and validity purposes. There is a vast need, to trace PR activities in CSR, from the initial planning stage, to determine whether these activities tally well with the corporate goals and objectivities, in serving the public, in a bid to create mutual understanding with the corporation. In this context, the question often asked on whether CSR programs are more than just a mere manoeuvre through which companies aim to acquire a positive public image, beat competition and run high, can be contested. We argue that CSR can be considered to be a new solution identified by the PR department, to improve the image of the organisation by appealing to the sentimental side of the public, in solving social problems. In Zimbabwe, the PR departments at Econet and NRZ, initiate and execute duties similar to what was observed by Clark (2000). He argued that CSR like PR seeks to represent an opportunity of improving the efficacy of activity of the corporate world.